A Compact Wideband Microstrip-Fed Planar Slot Antenna with Partial Defected Ground Structure for 2.7–12 GHz Wireless Applications - Rami Abduimawjood Mohammed; Uttam Laxman Bombale (Universitas Ahmad Dahlan, 2026)
This paper presents the design and numerical investigation of a compact wideband microstrip-fed planar slot antenna for broadband wireless communication applications. The antenna is designed on a low-cost FR-4 substrate with a compact planar configuration, making it suitable for space-constrained and economical wireless devices. In the initial design stage, a reference microstrip-fed antenna is developed and shown to operate from 3.25 to 11.6 GHz under the −10 dB impedance bandwidth criterion. The antenna is then optimized through a systematic trial-and-error parametric refinement process involving modifications of the radiator profile, feed-line geometry, slot configuration, and partial defected ground structure. To further enhance radiation performance, three compact rectangular parasitic directors are arranged in front of the main radiating structure with optimized spacing to improve forward radiation and gain. Full-wave electromagnetic simulations are carried out using Ansys High Frequency Structure Simulator (HFSS). The final optimized antenna achieves a continuous −10 dB impedance bandwidth from 2.7 to 12 GHz, covering the ultra-wideband (UWB) spectrum as well as several sub-6 GHz fourth-generation/fifth-generation (4G/5G) communication bands. The optimized antenna exhibits simulated gains of approximately 5.53 dB, 6.97 dB, and 6.19 dB at 6.7 GHz, 8.7 GHz, and 10.7 GHz, respectively, showing an overall improvement compared with the reference design. The radiation patterns remain reasonably stable across the investigated lower, middle, and upper frequency regions of the operating band, with quasi-omnidirectional characteristics and improved forward radiation due to the director elements. Compared with several reported wideband microstrip antenna designs, the proposed antenna offers a favorable combination of wide impedance bandwidth, compact structure, low-cost substrate realization, and enhanced gain. Therefore, the proposed antenna is a promising candidate for modern broadband wireless systems, including UWB and sub-6 GHz 4G/5G applications.